2000
DOI: 10.1080/03079450020016751
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, management and environmental triggers of the ascites syndrome: A review

Abstract: In meat-type chickens, an inadequacy of vascular capacity for blood flow through the lung to provide the tissues with the oxygen needed for rapid growth is the primary cause of pulmonary hypertensioninduced ascites. There are a variety of other factors that can trigger the ascites syndrome. These factors may cause increased blood flow because of a higher metabolic rate (cold, heat, certain nutrients, chemicals, etc.) or they may cause pulmonary hypertension-induced ascites in rapidly growing chickens because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
148
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(160 citation statements)
references
References 49 publications
6
148
1
5
Order By: Relevance
“…At sea level, oxygen makes up 20.9% of the atmosphere and the equivalent percentage of oxygen drops approximately 1% for every 500 m rise in altitude (Julian, 2000). The purpose of the present study was to test the hypothesis that there is a metabolic adaptation to environmental hypoxia in broiler chickens (Buys et al, 1998;Hassanzadeh et al, 2002).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…At sea level, oxygen makes up 20.9% of the atmosphere and the equivalent percentage of oxygen drops approximately 1% for every 500 m rise in altitude (Julian, 2000). The purpose of the present study was to test the hypothesis that there is a metabolic adaptation to environmental hypoxia in broiler chickens (Buys et al, 1998;Hassanzadeh et al, 2002).…”
Section: Introductionmentioning
confidence: 93%
“…Such occurrences among fast growing lines are even more apparent under conditions that impose an additional metabolic load on the birds, such as low ambient temperature and high altitude (Julian, 1993(Julian, , 2000Hassanzadeh et al, 2001Hassanzadeh et al, , 2003. This may not only be related to an increased oxygen demand, but also to the supply of oxygen that could be involved or altered in these lines selected for rapid growth and efficient food conversion (Decuypere et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In a cold environment, the growth rate is faster and metabolic rate rises to increase heat production and maintain normal body temperature (Julian, 2000). Consequently, cardiac output increases to supply the oxygen required for metabolism causing increased vascular pressure in the lung and pulmonary arteries (pulmonary hypertension).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, cardiac output increases to supply the oxygen required for metabolism causing increased vascular pressure in the lung and pulmonary arteries (pulmonary hypertension). Pulmonary hypertension triggers series of events, which finally lead to the ascites syndrome (Julian, 2000 and2007). During cold stress several studies have reported important physiological changes, including classic hematological changes and increased right ventricle weight per total ventricle weight (RV : TV) ratio (Yahav et al, 1997;Luger et al, 2003;Ipek and Sahan, 2006), but there is only very little or no information on the other physiological responses such as blood chemical alterations.…”
Section: Introductionmentioning
confidence: 99%
“…High altitude, poor ventilation (Julian, 2000), low temperature (Fathi et al, 2011), and ad libitum feeding (Rodríguez-Ortega et al, 2014) are predisposing factors for AS. High altitude reduces the partial pressure of oxygen (PO 2 ) in the inspired air (hypoxia, Wideman et al, 2013), which in turn produces hypoxic broilers (Ruiz-Feria & Wideman, 2001).…”
Section: Introductionmentioning
confidence: 99%